Religious Vocabulary in Demosthenes’ Speech Against Timocrates - Seres, Dániel (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In this study I argue that the words “ἱερόσυλος” (temple-robber) and “κατάρατος” (accursed) are key elements in Demosthenes’ speech against Timocrates. In both cases, I argue that in this speech elements of religious vocabulary are clearly used: Demosthenes legitimately and convincingly uses such strong expressions against his opponents. As these words rarely occur in texts of the classical period, I shell examine in parallel the prose texts of the fifth to third centuries BC, furthermore the epigraphical sources and the dramas, which are the primary requirements to understanding the role of these words in argument.